PERTUMBUHAN DAN PERBANYAKAN TUNAS MIKRO SINGKONG (Manihot esculenta CRANTZ.) SECARA IN VITRO PADA BERBAGAI KONSENTRASI BENZIL ADENIN. - Ardian, Ardian; Yuliadi, Erwin (JURNAL AGROTROPIKA, 2020)
Propagation of cassava through in vitro culture is required by farmers and agro industries to fulfill the need of the best and the newest clone as soon as after that clone is released by government. The objective of this research is to know the effect of the application of four concentration of benzyl adenine on the growth and proliferation of cassava shoot in vitro. Explants used were one-node cuttings of cassava about 1 cm length, grown in polybags. This research was arranged in completely randomized design with the treatments consisting of four concentrations of benzyl adenine: 0.5, 1, 2 and 4 mg/l added of basic media of Murashige and Skoog. Each treatment was replicated 4 times with 5 explants in each experimet al unit. The best growth and micro-shoot propagation of cassava in vitro was indicated by treatment of 0.5 mg/l benzyl adenine. Key words: cassava, benzyl adenin, in vitro, micro-shoot